A importância dos Fragmentos Florestais do campus da FCT/UNESP no contexto da mancha urbana no município de Presidente Prudente - SP - Melo, Felipe dos Santos de [UNESP] (2018)
The Forest Fragment of FCT-UNESP is part of the Permanent Preservation Area of the FCT-UNESP campus, located in the city of Presidente Prudente, in the region of Paranapanema, in the west of São Paulo state. We intend through this work prove that fragment has the necessary infrastructure to become a model of forest restoration to the other fragments present in the urban area of Presidente Prudente. Through the analysis of Environmental Licensing (Cut of Isolated Trees in Urban Land) at FCT/UNESP, dated October 2014.This process resulted in the removal of 26 native trees and an exotic tree and reforestation necessity of 650 native tree seedlings. The reforestation that took place in December 2014 and January 2015 suffered a total abandon by the campus administration and is in almost complete failure. Through the field analysis, historical surveying of occupation of the region and surveying of the anthropic processes that led to the non-development of the seedlings and gradual loss of the planted seedlings, this work proposes the participation of the academic community to execute the creation of the Committee on the Environment in the campus of FCT/UNESP, being responsible for manage the forest restoration of the fragment and creation of working groups for the environmental improvement on campus